Discursive heterogeneity in Robert Bontine Cunninghame Graham's travel account Mogreb-El-Acksa: A Journey in Morocco (1898) - Aammari, Lahoucine (ELOPE (Ljubljana), 2017)
Robert Bontine Cunninghame Graham is a less-examined British traveller who made his peregrinations into Western Barbary, or the "Land of the Furthest West" in the late nineteenth century, the era of full-blown empire. He reveals his solid support for the British Empire and its complex discursive apparatuses. Expressing his Orientalist desire to know Moroccans as Other, this traveller claims an epistemological mastery and narrative invasion over the field of his observation. However, the traveller is not a wholly root-and-branch imperialist; he is caught between narrative mastery and a fantasy of Western Barbary as a toponym, where his different desires can be validated and an image of Moroccan society as an impenetrable, concealed domain of inaccessibility and total invisibility. These paradoxical viewpoints reveal certain discursive "heterogeneities, inconsistencies and slippages" (Lowe 1991, 7) within Graham's travel account Mogreb-El-Acksa: A Journey in Morocco (1898).
Keywords: ambivalentnost; Cunninghame Graham, R. B., 1852-1936; diskurzivna heterogenost; kolonialni diskurz; literarne študije; orientalistična želja; potopis